Pengaruh Disiplin, Kesehatan dan Keselamatan Kerja terhadap Kinerja Pegawai Dimediasi Motivasi Kerja pada PT.PLN (Persero) Unit Pelaksana Pelayanan Pelanggan (UP3) Manado - Krhistian, Roy; Hasbiyadi, Hasbiyadi; Sohilauw, Muhammad Irfai (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the effect of work discipline and occupational health and safety (OHS) on employee performance with work motivation as a mediating variable at PT PLN (Persero) UP3 Manado. The research was motivated by the low Organizational Performance Score (NKO) in 2024 and the occurrence of workplace accidents in the unit. This research employed a quantitative approach with a causal explanatory design. A total of 103 permanent employees were selected as the sample using Slovins formula from a population of 186 employees. Data were collected through a five-point Likert scale questionnaire and analyzed using Partial Least SquaresStructural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that work discipline does not directly affect performance, but it has a significant positive effect on motivation. OHS significantly affects both performance and motivation. Motivation significantly affects performance and mediates the influence of discipline and OHS on performance. The mediation role of motivation is full in the relationship between discipline and performance, and partial in the relationship between OHS and performance. These findings highlight the crucial role of motivation as the main driver of employee performance. Therefore, performance improvement strategies at PLN UP3 Manado should focus on strengthening work discipline, implementing OHS, and enhancing employee motivation.